1996
DOI: 10.1046/j.1365-2265.1996.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium homeostasis in pregnancy

Abstract: The demands of fetal growth lead to an adaptation of maternal homeostasis in order to provide the required calcium from enhanced intestinal absorption rather than from mobilization of maternal skeletal reserves. In large part this adaptive process depends on the interrelationship between PTH and 1,25(OH)2D which shows quantitative rather than qualitative changes from the non-pregnant state. In contrast the maintenance of fetal mineral homeostasis largely depends on PTHrP which regulates active placental calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 20 publications
1
29
1
Order By: Relevance
“…The increased calcium demands during pregnancy are primarily meet via the enhanced maternal intestinal calcium absorption [21] related to increased Vit D1,25OH production [17], with a 2-fold increase in intestinal calcium absorption occurring during pregnancy [22]. In our patient, 1,25-dihydroxycholecalciferol levels were nearly twice the upper limit of the healthy subject range.…”
Section: Discussionmentioning
confidence: 77%
“…The increased calcium demands during pregnancy are primarily meet via the enhanced maternal intestinal calcium absorption [21] related to increased Vit D1,25OH production [17], with a 2-fold increase in intestinal calcium absorption occurring during pregnancy [22]. In our patient, 1,25-dihydroxycholecalciferol levels were nearly twice the upper limit of the healthy subject range.…”
Section: Discussionmentioning
confidence: 77%
“…The temporal changes in their concentrations are consistent with our current understanding of the way in which maternal calcium homeostasis adapts to provide calcium for the fetus. 12,28 The increase in bone turnover later in pregnancy would suggest that the body has an apparent lack of capacity to obtain the necessary calcium for fetal skeleton formation from dietary sources. It has been suggested that the gastrointestinal tract may not be able to increase calcium absorption adequately enough to provide this response.…”
Section: Discussionmentioning
confidence: 99%
“…However, because PTH concentration is lowered or unchanged in pregnant women, it is unlikely to be primarily responsible for the increase in 1,25(OH) 2 D seen in pregnancy (3) , although it remains responsive to changes in Ca load (147) . Although hormones, such as oestrogen, prolactin, growth hormone and insulin-like growth factor-I, have the ability to induce 1-a-hydroxylase activity (174,175,181) , it is likely that PTHrP has a key role (3,179,182) . This activates the PTH/PTHrP receptor and therefore exhibits PTH-like effects, including stimulation of renal 1,25(OH) 2 D production (182,183) .…”
Section: Regulation Of Calcium Metabolism In Pregnancy and Lactationmentioning
confidence: 99%
“…Although hormones, such as oestrogen, prolactin, growth hormone and insulin-like growth factor-I, have the ability to induce 1-a-hydroxylase activity (174,175,181) , it is likely that PTHrP has a key role (3,179,182) . This activates the PTH/PTHrP receptor and therefore exhibits PTH-like effects, including stimulation of renal 1,25(OH) 2 D production (182,183) . Increased concentrations of PTHrP are detected in the plasma of pregnant women, probably originating from fetal, placental and mammary tissues (4) , and its concentration rises by about two-fold from early to late pregnancy (110,176) .…”
Section: Regulation Of Calcium Metabolism In Pregnancy and Lactationmentioning
confidence: 99%